Sosialisasi Pengolahan Data Anggota Koperasi Dan Simpan Pinjam Untuk Meningkatkan Efisiensi dan Transparansi - Santi, Indyah Hartami; Kustanto, Kustanto (Penerbit Widina, Widina Media Utama, 2025)
The Mangoentanan Cooperative has significant potential for empowering its members economically. However, member data management and savings and loan transaction processes are still carried out conventionally (manual recording in a ledger), which carries a high risk of errors in calculations and inefficiencies. The purpose of this community service activity is to socialize and train the administrators and members of the Mangoentanan Cooperative in using a web-based application to digitize member data processing and savings and loan transactions. This activity applies a technology-based participatory approach, which combines theoretical socialization and direct practice (hands-on training) using a web-based cooperative application. The training focused on the administrators and members of the cooperative to ensure they have adequate technical skills in operating the new system. Evaluation of participant responses was conducted to measure acceptance and readiness to use the application. The evaluation results showed a very positive level of acceptance towards the application implementation. 85% of participants stated that the application facilitated transaction recording, and 78% stated that they were ready to use the application as the cooperative's main system. Furthermore, 90% of participants proposed further training to explore other features. The evaluation results showed a very positive level of acceptance towards the application implementation. 85% of participants stated that the application facilitated transaction recording, and 78% stated that they were ready to use the application as the cooperative's main system. Furthermore, 90% of participants proposed further training to explore other features. The digitalization of cooperatives through web-based applications has proven to accelerate and simplify the management of member data and savings and loan transactions, making the recording and reporting process more efficient, accurate, and accessible. The implementation of this technology substantially increases the transparency and accountability of cooperatives, as digital data supports easy auditing and the preparation of reliable, real-time reports.ABSTRAKKoperasi Mangoentanan memiliki potensi signifikan dalam pemberdayaan ekonomi anggota. Namun, pengelolaan data anggota dan proses transaksi simpan pinjam masih dilakukan secara konvensional (pencatatan manual di buku besar), yang berisiko tinggi menyebabkan kekeliruan dalam perhitungan dan inefisiensi. Tujuan dari kegiatan pengabdian masyarakat ini adalah untuk mensosialisasikan dan melatih pengurus serta anggota Koperasi Mangoentanan dalam menggunakan aplikasi berbasis web untuk digitalisasi pengolahan data anggota dan transaksi simpan pinjam Kegiatan ini menerapkan pendekatan partisipatif berbasis teknologi, yang mengombinasikan sosialisasi teoretis dan praktik langsung (hands-on training) menggunakan aplikasi koperasi berbasis web. Pelatihan difokuskan pada pengurus dan anggota koperasi untuk memastikan mereka memiliki keterampilan teknis yang memadai dalam mengoperasikan sistem baru. Evaluasi respons peserta dilakukan untuk mengukur penerimaan dan kesiapan penggunaan aplikasi. Hasil evaluasi menunjukkan tingkat penerimaan yang sangat positif terhadap implementasi aplikasi. Sebanyak 85% peserta menyatakan bahwa aplikasi tersebut memudahkan pencatatan transaksi, dan 78% menyatakan siap menggunakan aplikasi sebagai sistem utama koperasi. Selain itu, 90% peserta mengusulkan adanya pelatihan lanjutan untuk eksplorasi fitur-fitur lainnya Digitalisasi koperasi melalui aplikasi berbasis web terbukti mampu mempercepat dan mempermudah pengelolaan data anggota serta transaksi simpan pinjam, menjadikan proses pencatatan dan pelaporan lebih efisien, akurat, dan mudah diakses. Penerapan teknologi ini secara substantif meningkatkan transparansi dan akuntabilitas koperasi, karena data digital mendukung kemudahan audit dan penyusunan laporan real-time yang tepercaya.